2018
DOI: 10.1016/j.crvasa.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of acute ischemic stroke patients treated by direct catheter-based trombectomy depending on their baseline characteristics

Abstract: Úvod: Mechanická trombektomie (MT) se ukázala být účinnou léčebnou metodou u pacientů s akutní ischemickou cévní mozkovou příhodou (iCMP) vzniklou uzávěrem proximálního úseku velkých mozkových tepen. Cílem této studie bylo porovnat závažnost neurologického defi citu pacientů, kteří podstoupili MT v závislosti na jejich základních klinických charakteristikách. Metody: Prospektivní observační monocentrický registr pacientů léčených mechanickou trombektomií pro akutní iCMP. Stupeň neurologického defi citu byl kva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A total of 811 studies were identified and screened. Of these, 94 studies were assessed for eligibility, and 11 studies 5,9,10,[29][30][31][32][33][34][35][36] were included in the meta-analysis. We documented the reasons for the exclusion of nine eligible studies from the meta-analysis (Figure 1 and Supplement 3).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 811 studies were identified and screened. Of these, 94 studies were assessed for eligibility, and 11 studies 5,9,10,[29][30][31][32][33][34][35][36] were included in the meta-analysis. We documented the reasons for the exclusion of nine eligible studies from the meta-analysis (Figure 1 and Supplement 3).…”
Section: Resultsmentioning
confidence: 99%
“…36 These baseline comorbidities in patients with RI are independently associated with worse prognosis, death, and sICH. 37 The Laible 2021 study 14 19 and the Vavrova 2018 study 20 were also excluded from the sensitivity analyses because they did not report a detailed definition of RI. Moreover, the number of patients involved in these two studies was relatively small, which may explain why the results of the Wirtz 2019 study were quite different from those of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining 16 articles eligible for full-text screening, 1 article was excluded for considering the same source of study population as another study, and 4 were excluded for reporting outcomes other than those relevant to our study. Finally, 11 articles, [14][15][16][17][18][19][20][21][22][23][24] including 5053 patients with stroke receiving EVT, were included in the full analysis. The detailed process of article screening is shown in Figure 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation